Evaluating the Performance of Bank Syariah Indonesia Using the Maqashid Syariah Index - Riswanti, Novi; Setiyaningsih, Titik Agus; Hartutik, Hartutik (Asean International Journal of Business, 2025)
This study aims to evaluate the performance of Bank Syariah Indonesia (BSI) using the Maqashid Syariah Index for the period 2021-2023. The findings reveal a significant decline in the index, from 6.91 in 2021 to 4.11 in 2023, highlighting the need for improvements in educating individuals, promoting justice, and preserving public welfare. While educational grant ratios have improved, the quality of training programs requires enhancement. In the justice aspect, a decline in equitable transactions underscores the necessity for policy evaluations to ensure transparency and compliance with Sharia principles. Furthermore, although profitability has increased, investments in vital sectors have decreased, necessitating more robust investment strategies. The implications of this study include strengthening CSR programs, enhancing transparency in Sharia reporting, improving financial literacy, and developing Sharia-aligned business strategies. This research contributes to the Maqashid Syariah literature and serves as a performance evaluation framework to enhance customer trust and societal welfare. Future studies should consider external factors and develop holistic theoretical models.